-3+6(2x-1)=12x-9

Simple and best practice solution for -3+6(2x-1)=12x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+6(2x-1)=12x-9 equation:



-3+6(2x-1)=12x-9
We move all terms to the left:
-3+6(2x-1)-(12x-9)=0
We multiply parentheses
12x-(12x-9)-6-3=0
We get rid of parentheses
12x-12x+9-6-3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| f(3)=9(3)-17 | | 9.4=-t/1.5 | | 2(-7x+8)=16-14x | | 2x-12-5x=x+3+x | | 2x-122x-12-5x=x+3+x | | 2(4w+5)/5=9 | | 20x-20+12x=14-2x | | 3x-11=69 | | 3r-12-8r+210=180 | | 1/8(x-10)=4+x | | -2(7x+6)=-12-14x | | 3x=4+28 | | 4(m-1)=8(m-1)+12 | | 9v+54=18v | | y/10-3=5 | | x+24+2x=2-2x-4 | | -5-19p=-17p-13-2p | | 1(2y+-1)=-9 | | 6+15x=-3(-5x-2) | | -8u-8=-4(u+6) | | 8(s-3)=-84 | | 4+2x=2(-x+2)-8 | | b-4/2=b+1/4 | | 6+15x=-3 | | 6-4n=-409 | | -14x+11-11=-17-14x | | 6-4n=-409 | | 3x-4-4x=3x-4-2x-6x | | -20+x=20+20-9x | | 48=-v+188 | | 36-x=192 | | -8x-19=-4-15-8x |

Equations solver categories